The Improvement of Functional State of Brain Mitochondria with Astaxanthin in Rats after Heart Failure - Baburina, Yulia; Krestinin, Roman; Fedorov, Dmitry; Odinokova, Irina; Pershina, Ekaterina; Sotnikova, Linda; Krestinina, Olga (International journal of molecular sciences, 2022)
The relationship between neurological damage and cardiovascular disease is often observed. This type of damage is both a cause and an effect of cardiovascular disease. Mitochondria are the key organelles of the cell and are primarily subject to oxidative stress. Mitochondrial dysfunctions are involved in the etiology of various diseases. A decrease in the efficiency of the heart muscle can lead to impaired blood flow and decreased oxygen supply to the brain. Astaxanthin (AST), a marine-derived xanthophyll carotenoid, has multiple functions and its effects have been shown in both experimental and clinical studies. We investigated the effects of AST on the functional state of brain mitochondria in rats after heart failure. Isoproterenol (ISO) was used to cause heart failure. In the present study, we found that ISO impaired the functional state of rat brain mitochondria (RBM), while the administration of AST resulted in an improvement in mitochondrial efficiency. The respiratory control index (RCI) in RBM decreased with the use of ISO, while AST administration led to an increase in this parameter. Ca2+ retention capacity (CRC) decreased in RBM isolated from rat brain after ISO injection, and AST enhanced CRC in RBM after heart failure. The study of changes in the content of regulatory proteins such as adenine nucleotide translocase 1 and 2 (ANT1/2), voltage dependent anion channel (VDAC), and cyclophilin D (CyP-D) of mitochondrial permeability transition pore (mPTP) showed that ISO reduced their level, while AST restored the content of these proteins almost to the control value. In general, AST improves the functional state of mitochondria and can be considered as a prophylactic drug in various therapeutic approaches.